Pengaruh Endorse Influencer Fadil Jaidi Terhadap Minat Beli Konsumen - Putri Rifiani; Firdaus Yuni Dharta; Oky Oxcygentri (Peneliti.net, 2022)
The background of the research made by this author is the unique way of endorsements carried out by influencer Fadil Jaidi on Instagram social media. With the aim of knowing how much credibility and influence the endorsement of Fadil Jaidi as an influencer on consumers' buying interest. This research uses quantitative methods and conducts surveys through explanatory surveys. The theory used is the Source Credibility Theory, which is based on the object of his research is the social media followers of Instagram @fadiljaidi. The data collection techniques used are questionnaires and literature research, with descriptive statistical data analysis techniques, namely simple linear regression analysis. The results of this study are that the intensity and attractiveness of endorsements have a significant effect while the content of the endorsement message does not have a significant effect on consumers buying interest.